(untitled) (Research, Society and Development, 2021)
Objective: to identify in the literature the factors that influence the transfer of effective intra-hospital care by the nursing team. Methodology: this is an integrative literature review, carried out in three databases: Web of Science, Medical Literature Analysis and Retrieval System Online (MEDLINE) and Sci Verse Scopus (SCOPUS). Primary studies were included, in Portuguese, Spanish or English, published between the years 2015 to 2021. Results: the careful analysis of 39 international studies made it possible to identify that transfers related to adult and pediatric patients and carried out through the displacement or not of the patient in the intra-hospital environment are influenced by factors such as communication, transport, teamwork and health education, and these impact on the effectiveness of the transfer of intra-hospital care. Conclusion: in view of the analysis of the studies found, communication is seen as a predominant factor, although the transport, teamwork and health education factors also present significant characteristics that influence the realization of effective intra-hospital care transfer.